(untitled) (Research, Society and Development, 2020)
The objective of the study was to evaluate the water quality of Tupé beach and to classify it according to the standards and criteria determined by the Resolution of the National Environment Council nº 274/2000 and 357/2005. Water collections were carried out for five consecutive weeks in two seasonal periods (high and low water), using the technique of multiple tubes and portable equipment. Point one on Tupé beach was classified as unsuitable in the dry season and the other points were classified as suitable for both periods. In general, the physical and chemical parameters were within the standards established by the current environmental resolution. It is worth mentioning the regional characteristics of each study region, such as the acidity of the waters of the Negro river. There was no significant difference between points at Tupé beach, with p = 0.6198.